Evaluation of Uropathogenic Infections and Antibiotic Susceptibility Profiles of Bacteria in Patients at the CHU Ignace Deen National Hospital, Conakry (Republic of Guinea) - Camara, Taliby Dos; Makanera, Abdoulaye; Rachid, Mounaida; Camara, Mory (Research Perspectives of Microbiology and Biotechnology Vol. 2, 2024)
Urinary tract infections (UTIs) are a major public health problem worldwide. Numerous microorganisms are associated with these infections. The aim of this study was to determine the antibiotic sensitivity of different bacterial species isolated from UTIs. This prospective and cross-sectional descriptive study took place over a three months period, from 2 February to 2 May 2022. Bacterial identifications showed a predominance of Escherichia coli (52%), followed by Klebsiella pneumoniae (13%), Enteroccus spp. (9%), Enterobacter cloacae complex (8%) and Staphylococcus aureus (8%). The antibiogram showed that certain antibiotics were active on the majority of strains, including imipenem (75%), cefoxitin (65%) and ertapenem (64%), amikacin (61%). The most affected age groups by UTI were those of 51 years and over (54%), followed by those of 25 to 50 years (28%). According to Marital status, the highest prevalence of UTIs concerned Married people (78%), whereas the socio-professional characteristics showed that Housewives were the most represented (30%). The majority of infected patients came from the Commune of Ratoma (35%). An effective fight against these UTIs requiring, among other means of treatment, the identification of the germs involved in these infections and the performance of their antibiograms.